War is--- : soldiers, survivors, and storytellers talk about war - Aronson, Marc.; Campbell, Patricia J. (Cambridge, MA : Candlewick Press, 2008)
A collection of essays, memoirs, letters, and fiction that present opposing viewpoints on the nature of war by such contributors as Mark Twain, Bob Dylan, and Ernie Pyle.
Includes bibliographical references (p. 196-199).
Kirkus Review.
Young Adult
Keywords: American literature -- 20th century; War -- Literary collections; American literature -- 20th century; War -- Literary collections